2 A hierarchal analysis of eligibility for PCSK9 inhibition in Ireland: bridging the divide between the NCPE managed access protocol and ESC/EAS guidelines. (30th September 2020) - Waters, M; Coughlan, JJ; O'Connor, C; Maher, V
Abstract : Introduction: In 2019, the national center for pharmacoeconomics (NCPE) released a managed access protocol (MAP) for the prescribing of proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) in Ireland. To be eligible for a PCSK9i, patients must have had a myocardial infarction or coronary artery bypass grafting, LDL of >4.0 mmol/L, treated with high dose statin and ezetimibe. In contrast, the 2019 ESC/EAS guidelines on the management of dyslipidemias recommend that patients at 'very high risk' with an LDL-C of >1.4 mmol/L on a maximally tolerated dose of a statin and ezetimibe, be considered for PCSK9i. We aimed to define the proportion of patients who are suitable for a PCSK9i following completion of cardiac rehabilitation based on these criteria. Method: We retrospectively analysed data on patients undergoing cardiac rehabilitation in our center from January 2018 to December 2019. We then applied the NCPE MAP and the ESC/EAS criteria to assess eligibility for a PCSK9i in the cohort. 'Very high risk' was defined as documented atherosclerotic coronary artery disease as per ESC dyslipidaemias guidelines. Results: The analysis includes 299 patients, who had complete lipid profiles at baseline and 6 months of follow-up, and who have a history of coronary artery disease. Baseline characteristics, mean age 62.5 years, 76% male. 202 (67.6%) patients had a history of MI or CABG making them eligible for a PCSK9i based on NCPE clinical criteria. Only 1 patient (0.5%) in this group was on a high dose statin, ezetimibe and had a 6 month LDL-C of >4.0 mmol/L making them eligible for a PCSK9i as per NCPE MAP criteria. In contrast to the NCPE MAP criteria all 299 patients were deemed eligible for a PCSK9i based on ESC/EAS clinical criteria of 'very high risk'. 160 patients (53.5%) had an LDL-C level >1.4 mmol/L at 6 months despite maximally tolerated statin therapy, mean LDL-C 2.29 mmol/L. Only a minority of patients in this cohort were on ezetimibe, 30/160 (18.7%), however previous studies have shown that on average ezetimibe reduces LDL-C by 25% in combination with statins. Based on this, we sought to define the cohort who would potentially be eligible if they had been on ezetimbe and experienced a 25% reduction in LDL-C. 81/160 patients had a 6-monthly LDL-C >1.8 mmol/L and were on high dose statin therapy, we included these patients in our final analysis, resulting in 37.1% (111/299) patients in our cohort being eligible for a PCSK9i based on current ESC guidelines, results are summarized in figure 1 . Discussion: Our results highlight the discrepancy between current ESC/EAS guidelines and the reimbursement criteria for PCSK9i in Ireland. This discrepancy results in minimal patients with coronary artery disease being eligible for a PCSK9i in Ireland. The results also highlight that a significant proportion of patients in clinical practice do not meet LDL-C goals post cardiac rehabilitation, these targets should be met in order to reduce future cardiovascular risk and improve outcomes for patients.